OP68 An Evidence-Based Clinical Pathways Program Reduces Low-Value Care. (2017) - Mull, Nikhil; Leas, Brian; Mitchell, Matthew; Lavenberg, Julia; Patel, Neha; Williams, Austin; Umscheid, Craig
Abstract : INTRODUCTION: Misdiagnosis of asymptomatic bacteriuria as catheter-associated urinary tract infection (CAUTI) leads to unnecessary tests and other low-value care. We used this topic as the prototype to develop a clinical pathways program to promote evidence-based decision making in a multi-hospital system. METHODS: We convened a task force including hospital and critical care physicians, nurses, laboratory staff, and informatics specialists. Our Health Technology Asessment (HTA) center completed a rapid systematic review on guidelines and algorithms for diagnosing CAUTI. Additional rapid reviews were completed as necessary to address specific follow-up questions. A draft pathway based on the guidelines was developed, and then the task force edited it in an iterative process. We used the Dorsata platform (Dorsata Inc., Washington, DC) to create, distribute and maintain the pathway. Dorsata has both desktop and mobile interfaces that guide clinicians through decision algorithms. Individual pathways include links to references and a portal for direct user feedback. Pathway owners have access to a real-time pathway utilization dashboard. A standardized order set with the pathway was added to our electronic health record system. We also held educational meetings for residents and provided "huddle sheets" to nurse educators at each hospital. Posters and computer screen savers were also used to raise awareness of the new pathway. RESULTS: We now have a total of 111 pathways on Dorsata, developed following the same model as the CAUTI evaluation pathway. Some topics, like breast cancer, have as many as sixteen pathways, addressing different clinical questions like first- and second-line therapy. Over 600 individuals have registered for the mobile app, including attending and resident physicians, nurses, and medical students. The pathway site had 1, 619 views in December 2016, the most recent month for which complete records are available. The pathways are proving to have an effect on clinical decision making. For example, the annualized number of unnecessary urine cultures avoided as a result of the pathway is 4, 474; resulting in estimated direct cost savings of USD67, 110. CONCLUSIONS: Using pathways to present HTA information at the point of care is feasible and can improve the value of care.